EFEKTIVITAS APLIKASI PUPUK ORGANIK CAIR LENGKAP DAN PUPUK ANORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI - Didik Raharjo; Edi Tando; Mutiara Kusumaningtyas Pitaloka; Hafnah Khilwatul Ilmi; Istiqomah Istiqomah (AGRORADIX : Jurnal Ilmu Pertanian, 2022)
The need for food is currently increasing so that to meet food needs, agricultural land, both dry land and paddy fields, is needed. Rice fields in Southeast Sulawesi are quite extensive, but rice productivity is still low. The use of inorganic fertilizers continuously for a long time, results in damage to the physical properties of the soil. The purpose of the study was to determine the effectiveness of the application of complete liquid organic fertilizer packages and inorganic fertilizers on the growth and yield of paddy rice. The study used a randomized block design (RAK) with 5 fertilization treatments and 3 replications. The results showed that inorganic fertilization with a dose of 50% Local fertilizer recommendation + POCL fertilizer package had a significant effect on the number of tillers, number of productive tillers, empty grain and filled grain and yielded 6.52 tons/ha GKG. Farming analysis on the treatment of reducing inorganic fertilizers by 50% from the local fertilizer recommendation and added to the POCL fertilizer package gave a greater profit of Rp.17,870,905.